Pertumbuhan Rumput Kerbau (Paspalum conjugatum Berg.) yang Diinokulasi Beberapa Dosis Fungi Mikoriza Arbuskular (FMA) pada Media yang Mengandung Merkuri (Hg) - Putri Seti Ayu; Zozy Aneloi Noli; Solfiyeni Solfiyeni (Jurnal Biologi Universitas Andalas, 2015)
The research about the growth of Buffalo Grass (Paspalum conjugatum Berg.) inoculated with several doses of Arbuscular Mychorrizal Fungi (AMF) ) in Media Containing with Mercury (Hg) had been done from February to July 2014 at the greenhouse, Plant Physiology and Tissue Culture Laboratory, Biology Department, Faculty of Mathematic and Natural Science and Environmental Laboratory, Faculty of Engineering, Andalas University. The aims of the research to know ability of P. conjugatum inoculated with several doses AMF in media containing with mercury and find the best dose of AMF for growh of P. conjugatum. The research used a Completely Randomized Design with five treatments and five replications. The treatments were control 0, 5, 10, 15, 20 g  AMF. The result showed that no effect inoculated of AMF up to 20 g to the height, number of leaves and dry weight of P. conjugatum.